ANALISIS SCENE FILM PEREMPUAN BERKALUNG SORBAN DALAM MENCIPTAKAN PROSES IDENTIFIKASI YANG MENUNJANG DRAMATIKA FILM - Sustia Mei Darta (Institut Seni Budaya Indonesia Bandung, 2023)
ABSTRACT Film stories are built from a combination of several actions carried out by film characters. Actions carried out by film characters can create an identification process. The identification process generally occurs in the audience when the audience feels sympathy for the main character, emotionally the audience feels what they are experiencing. One of the identification processes occurred in the film